Hemoglobin glycation index and all-cause mortality in adults: insights from a decade-long prospective cohort study - Yue-Yang Zhang; Yue-Yang Zhang; Yue-Yang Zhang; Yue-Yang Zhang; Yue-Yang Zhang; Wen-Yan Li; Wen-Yan Li; Wen-Yan Li; Wen-Yan Li; Wen-Yan Li; Wen-Yan Li; Qin Wan; et al. (Frontiers in Endocrinology)
BackgroundThe hemoglobin glycation index (HGI), an indicator of individual differences in glucose metabolism. This study undertakes a detailed 10-year cohort analysis to investigate the potential association between HGI and all-cause mortality in a Chinese adult population.MethodsBaseline data encompassing lifestyle and metabolic parameters were collected from 10,008 participants, with a subsequent 10-year follow-up. Following exclusions based on predefined criteria, 9,084 individuals were included in the final analysis. Participants were categorized into quartiles based on their HGI values. A suite of statistical tools, including Kaplan-Meier survival analysis, Cox proportional hazards models, restricted cubic splines (RCS), threshold effect models, and subgroup analyses, was employed to investigate the association between HGI and all-cause mortality.ResultsDuring the 10-year follow-up period, a total of 514 all-cause mortality cases were recorded. Kaplan-Meier survival analysis identified the Q2 group as having the lowest mortality rate. Fully adjusted Cox proportional hazards models demonstrated significant associations, indicating higher all-cause mortality risks in participants with both extremely low and high HGI levels compared to the Q2 group. RCS analysis further illustrated a U-shaped relationship between HGI and all-cause mortality.ConclusionsIn the Chinese population, both markedly elevated and significantly reduced HGI levels are associated with adverse impacts on long-term survival.Core tipThe aim of this study was to assess the association of Hemoglobin Glycation Index(HGI) with all-cause mortality in non-type 2 diabetic patients based on a 10-year cohort study from China. After COX regression, restricted cubic spline analysis, and subgroup analyses, it was found that a significant increase or decrease in HGI adversely affected long-term survival.